PENERAPAN MODEL PEMBELAJARAN PROBLEM BASED LEARNING UNTUK MENINGKATKA MOTIVASI BELAJAR SISWA KELAS V UPT SPF SDN MANCCINI II - Nurul Fitrasari; Sherly (STKIP Subang, 2024)
This research aims to increase the learning motivation of class V students at UPTS PF SDN MACCINI II. This research is Classroom Action Research (PTK). Eachc ycle is carried out for three meetings. The subjects of this research were class V UPT SPF SDN MACCINI II students, totaling 24 students consisting of 16 boysa nd 8 girls. Data collection methods used include observation, questionnaires andd ocumentation. Data analysis techniques were carried out descriptively,q uantitatively and qualitatively. Indicators of student success are characterized by student learning motivation which is said to increase if the average percentage is obtained at a minimum of 75% for each indicator. The results of this research indicate that the application of the problem based learning model to increase the learning motivation of class V students at UPT SPF SDN MACCINI II, namely that the average implementation of learning in cycle I was (63%) and was in the sufficient category and the implementation of learning in cycle II was (63%) (77%) and is in the good category. The average student learning activity in cycle I was (44%) in the medium category and student learning activity in cycle II was (77%) in the high category. There was an increase in learning motivation for class V UPT SPF SDN MACCINI II students after implementing the Problem Based Learning learning model. This is proven by the average student learning motivation score in cycle I is (50%) or in the sufficient category and the average student learning motivation score in cycle II is (80%) or in the very high category. Thus it can be concluded that the application of the Problem Based Learning learning model can increase the learning motivation of class V students at UPT SPF SDN MACCINI II